Does Corruption Affect Foreign Direct Investment? Empirical Evidence from ASEAN Plus Three Countries - Erni Panca Kurniasih; Djihan Islahiyah; Sri Kurniawati; Ichsan Iqbal (Journal of Economics, Business, and Accountancy Ventura, 2023)
Corruption poses a significant challenge in numerous countries, impacting foreign investment, including those within the ASEAN Plus Three (APT) region. This study aims to ascertain the influence of corruption and other factors—specifically, the exchange rate, political stability, and economic growth—on the appeal of foreign direct investment in APT countries. The research employs the Error Correction Model (ECM) for statistical testing to analyze both short- and long-term effects. The findings indicate that corruption and exchange rate fluctuations do not exert a significant impact on foreign investment inflows into APT countries, regardless of the time horizon. In the short term, a surge in corruption cases tends to diminish the interest of potential foreign direct investors. However, over the long term, foreign investors anticipate that APT countries will adopt more stringent measures to combat corruption, thus fostering a corruption-free environment. This expectation is bolstered by the presence of political stability and robust economic growth in APT countries, which stand as pivotal considerations for foreign direct investment. Therefore, APT countries, particularly Indonesia, ought to establish transparent investment guidelines, root out corruption, ensure political stability, maintain exchange rate stability, and prioritize policies aimed at stimulating economic growth in order to entice foreign investment.